Natural Formulations: Novel Viewpoint for Scleroderma Adjunct Treatment - Echeverria-Morgado, J (Hindawi Limited, 2021)
Background. Scleroderma is a complex disease involving autoimmune, vascular, and connective tissues, with unknown etiology that can progress through any organ systems. Objective. Yet, no cure is available; the thorough treatment of scleroderma and current treatments are based on controlling inflammation. Nowadays, medicinal plants/natural-based formulations are emerging as important regulators of many diseases, including autoimmune diseases. Here, we provided an overview of scleroderma, also focused on recent studies on medicinal plants/natural-based formulations that are beneficial in scleroderma treatment/prevention. Methods. This study is the result of a search in PubMed, Scopus, and Cochrane Library with "scleroderma", "systemic sclerosis", "plant", "herb", and "phytochemical"keywords. Finally, 22 articles were selected from a total of 1513 results entered in this study. Results. Natural products can modulate the inflammatory and/or oxidative mediators, regulate the production or function of the immune cells, and control the collagen synthesis, thereby attenuating the experimental and clinical manifestation of the disease. Conclusion. Natural compounds can be considered an adjunct treatment for scleroderma to improve the quality of life of patients suffering from this disease. © 2021 Shirin Assar et al.